Reconstruction of the Business Legal System in Encountering the Complexity of Maritime Goods Distribution Disputes Including Business Competition, Transportation Responsibility and Problematic Receivables - Le Nie; Dwi Kusumo Wardhani (Journal Customary Law, 2026)
The study aims to analyze and reconstruct the business legal system in addressing the complexity of maritime goods distribution disputes in Indonesia, involving aspects of business competition, transportation liability, and problem receivables. The research employs a normative juridical approach, combining statutory and conceptual perspectives through a review of norms in the Civil Code, the Commercial Code, and Law Number 5 of 1999 regarding the Prohibition of Monopolistic Practices and Unfair Business Competition. The results indicate disharmony and conflicting norms between legal regimes, leading to legal uncertainty and weak protection for business actors, particularly distributors in the maritime distribution chain. Empirical issues such as violations of distribution areas, price wars, damage to goods by porters, and problem receivables with disproportionate payment schemes demonstrate that existing law is not yet adaptive to modern business practices. Therefore, an integrative reconstruction of the business legal system is necessary through regulatory harmonization, which strengthens the principles of justice and legal certainty, and establishes a regulatory model capable of accommodating the interrelationships between contracts, transportation, business competition, and financing